Genetic diversity of Salmonella Paratyphi A isolated from enteric fever patients in Bangladesh from 2008 to 2018 - Rahman, SIA; Nguyen, TNT; Khanam, F; Thomson, NR; Dyson, ZA; Taylor-Brown, A; Chowdhury, EK; Dougan, G; Baker, S; Qadri, F (Public Library of Science, 2021)
Background The proportion of enteric fever cases caused by Salmonella Paratyphi A is increasing and may increase further as we begin to introduce typhoid conjugate vaccines (TCVs). While numerous epidemiological and genomic studies have been conducted for S. Typhi, there are limited data describing the genomic epidemiology of S. Paratyphi A in especially in endemic settings, such as Bangladesh. Principal findings We conducted whole genome sequencing (WGS) of 67 S. Paratyphi A isolated between 2008 and 2018 from eight enteric disease surveillance sites across Bangladesh. We performed a detailed phylogenetic analysis of these sequence data incorporating sequences from 242 previously sequenced S. Paratyphi A isolates from a global collection and provided evidence of lineage migration from neighboring countries in South Asia. The data revealed that the majority of the Bangladeshi S. Paratyphi A isolates belonged to the dominant global lineage A (67.2%), while the remainder were either lineage C (19.4%) or F (13.4%). The population structure was relatively homogenous across the country as we did not find any significant lineage distributions between study sites inside or outside Dhaka. Our genomic data showed presence of single point mutations in gyrA gene either at codon 83 or 87 associated with decreased fluoroquinolone susceptibility in all Bangladeshi S. Paratyphi A isolates. Notably, we identified the pHCM2- like cryptic plasmid which was highly similar to S. Typhi plasmids circulating in Bangladesh and has not been previously identified in S. Paratyphi A organisms. Significance This study demonstrates the utility of WGS to monitor the ongoing evolution of this emerging enteric pathogen. Novel insights into the genetic structure of S. Paratyphi A will aid the understanding of both regional and global circulation patterns of this emerging pathogen and provide a framework for future genomic surveillance studies.